A Bibliography of South African Languages, 2008-2017 With an Introduction by Menán du Plessis - van der Veken, Eline; Genis, René; Aarssen, Anne (Brill, 2018)
This concise bibliography on South-African Languages and Linguistics was compiled on the occasion of the 20th International Congress of Linguists in Cape Town, South Africa, in July 2018. The selection of titles is drawn from the Linguistic Bibliography and gives an overview of scholarship on South African language studies over the past 10 years.